2017
DOI: 10.1126/science.aah6171
|View full text |Cite
|
Sign up to set email alerts
|

Lipid transport by TMEM24 at ER–plasma membrane contacts regulates pulsatile insulin secretion

Abstract: INTRODUCTION Insulin is secreted by pancreatic β cells in response to glucose stimulation. Its release is controlled by the interplay of calcium and phosphoinositide signaling pathways. A rapid release phase, in which insulin containing granules that are already docked and primed at the plasma membrane (PM) undergo exocytosis, is followed by slow release. In this second phase, granules are docked and primed and then released in a series of bursts, each triggered by a spike in cytosolic Ca2+. RATIONALE To bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
244
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(248 citation statements)
references
References 71 publications
2
244
2
Order By: Relevance
“…Heavy liposomes were reconstituted with Sar1 buffer supplemented with 0.75 M sucrose and were extruded through a 0.4-μm filter. Liposome-tethering assays and liposome-aggregation experiments (determined by measuring absorbance at 405 nm) were based on previous work (57,93) and are described in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy liposomes were reconstituted with Sar1 buffer supplemented with 0.75 M sucrose and were extruded through a 0.4-μm filter. Liposome-tethering assays and liposome-aggregation experiments (determined by measuring absorbance at 405 nm) were based on previous work (57,93) and are described in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…To directly test whether TFG is capable of capturing COPII-coated vesicles, we developed an in vitro assay using two types of synthetic liposomes (Fig. 7A) (57). One set of "heavy" liposomes (∼250 nm in diameter) was generated in the presence of sucrose to enable facile sedimentation upon low-speed centrifugation and contained lipids that bind polyhistidine-tagged proteins (DOGS-NTA-Ni) with high affinity.…”
Section: Tfg Facilitates the Export Of Conventional Cargoes From The Ermentioning
confidence: 99%
“…Moreover, Sec22b, a non-fusogenic ER SNARE protein which can interact with the PM SNARE Syntaxin 1 at the PM, may contribute to ER-PM tethering and PM expansion in neurons [169]. Recently, TMEM24, a SMP domain-containing ER membrane protein highly expressed in brain, neurons, and insulinoma cells, has been shown to localize to ER-PM junctions and contribute to insulin secretion [170]. …”
Section: Recent Advances In Understanding the Regulation And Functmentioning
confidence: 99%
“…Karin Reinisch (Yale University, New Haven, USA) showed that the SMP-containing protein TMEM24 transports phosphatidylinositol in a Ca 2+ -dependent manner and explained how this regulates slow pulsatile insulin release (Lees et al, 2017). The breadth of the presented work clearly illustrates that direct organelle contacts are a key organizing principle that contributes to lipid diversity.…”
Section: Organelles Display Unprecedented Levels Of Interaction and Ementioning
confidence: 81%